Austerity Talk and Crisis Narratives: Memory Politics, Xenophobia, and Citizenship in the European Union - Hallgrimsdottir, Helga K.; Finnsson, Ari; Brunet-Jailly, Emmanuel (Frontiers in Sociology, 2020)
The focus in this paper is on understanding the complex intersections between crises and memory politics in shaping conversations about citizenship through an examination of the two defining crises of our time: the global financial crisis (GFC) of 2008 and the migrant crisis in Europe (starting in 2011 and continuing). The paper looks at these crises as narrative devices that intersect with memory politics in ways that heighten and intensify xenophobic and nationalist anxieties. The paper’s discussion is primarily theoretical, complemented with evidence drawn from public statements and policy platforms of three key right-wing Eurosceptic parties in the United Kingdom, France, and Germany (the United Kingdom Independence Party (UKIP), the Rassemblement National (RN), and the Alternativ für Deutschland (AfD).